2017
DOI: 10.3389/fvets.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Vaccination Targets for Stray Dog Populations

Abstract: The role of stray dogs in the persistence of domestic dog rabies, and whether removal of such dogs is beneficial, remains contentious issues for control programs seeking to eliminate rabies. While a community might reach the WHO vaccination target of 70% for dogs that can be handled, the stray or neighborhood dogs that are too wary of humans to be held are a more problematic population to vaccinate. Here, we present a method to estimate vaccination targets for stray dogs when the dog population is made up of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Multiple different measures were reported to assess effects on public health risk, again making it difficult to compare methods directly. Culling had decreasing effects on the various indicators of public health risk in both observational [105,106] and modelling studies [91,[100][101][102]107,108]. This contradicts previous literature suggesting that culling is ineffective at controlling disease in free-roaming dogs [115,116].…”
Section: Investigated Methods and Reported Effects Of Dog Population mentioning
confidence: 60%
See 3 more Smart Citations
“…Multiple different measures were reported to assess effects on public health risk, again making it difficult to compare methods directly. Culling had decreasing effects on the various indicators of public health risk in both observational [105,106] and modelling studies [91,[100][101][102]107,108]. This contradicts previous literature suggesting that culling is ineffective at controlling disease in free-roaming dogs [115,116].…”
Section: Investigated Methods and Reported Effects Of Dog Population mentioning
confidence: 60%
“…In addition, culling decreased both dog rabies prevalence [100,101] and the basic reproductive number of rabies [91,107,108] in modelling studies. However, when disease control through vaccination was included in the analysis, all papers in the final corpus reported that culling was not as effective as vaccination alone [91,102,107,108] or combined vaccination and fertility control [100]. The prevalence of Echinococcus granulosus in humans, livestock, and dogs decreased where culling was combined with fertility control [103,104].…”
Section: Investigated Methods and Reported Effects Of Dog Population mentioning
confidence: 99%
See 2 more Smart Citations
“…However, vaccination can only be done for owned animals. With a high number of stray animals, like dogs, in Africa, both approaches (quarantining and immunization) may not prove effective for control of infections like rabies, for example (Leung and Davis 2017;Salomão et al 2017).…”
Section: Control In Animalsmentioning
confidence: 99%